THE USE OF CANNABIDIOL IN NEURODEGENERATIVE PATHOLOGIES AND THE ROLE OF THE PHYSIOTHERAPIST - Alves, Alyara Jotaci Rodrigues; Lopes, Carla Carolina Ferreira; de Almeida, Fernando Cláudio; Nascimento, Fernanda Duarte; de Oliveira, Inglasse Ester; de Souza, Jaqueline Soares; de Souza, Micaelle Silva; Roberto, Nathália da Cruz; Maduro, Larissa de Souza; Silva, Sandra Rosa do Nascimento; de Abreu, Juscélio Clemente; Reis, Juliana Carvalho (Seven Editora, 2024)
The document explores the use of cannabidiol (CBD) in the treatment of neurodegenerative pathologies, highlighting its therapeutic potential in conditions such as epilepsy, multiple sclerosis, Parkinson's and Alzheimer's disease. CBD, a non-psychoactive compound from the Cannabis sativa plant, interacts with the endocannabinoid system, exhibiting anti-inflammatory, neuroprotective, and anxiolytic properties. In physiotherapy, CBD emerges as a complementary approach that can improve functionality, reduce neuropathic pain and spasticity, as well as contribute to the control of motor and behavioral symptoms associated with these diseases. The work also addresses challenges related to response variability, lack of standardization of dosages, and the need for more long-term research. Regulations from agencies such as COFFITO and ANVISA are mentioned, reinforcing the safety and applicability of CBD by trained physiotherapists. The study concludes that CBD has significant potential, but that scientific and regulatory barriers still need to be overcome for its full integration into clinical treatments. DOI:https://doi.org/10.56238/sevened2024.037-068